Absence of Cysteine and Iron Chelation Induces Ferroptosis in Triple-Negative Breast Cancer Cells - Manvi Agarwal Neeraj; JunJeong Choi (Breast Cancer: Basic and Clinical Research)
Background: Ferroptosis is a recently studied form of programmed cell death characterized by lipid peroxides accumulation in the cells. This process occurs when a cell’s antioxidant capacity is disturbed resulting in the inability of the cell to detoxify the toxic peroxides. Two major components that regulate ferroptosis are cysteine and iron. Objective: This study aimed to determine the effect of cysteine deficiency and iron chelation on triple-negative breast cancer (TNBC) ferroptosis in a lipid-enriched microenvironment. Design: The study has a laboratory-based experimental design. This study used the MDA-MB-231 cell line in various in vitro cell culture systems to investigate the research question. Methods: For the first part of the study, we subjected MDA-MB-231 cells to grow in cysteine-absent adipocyte-conditioned media. In the second half, we treated MDA-MB-231 cells with iron chelator, deferoxamine. BODIPY imaging and western blot were carried out to observe ferroptosis in the cells under the 2 conditions. Results: The results showed that cysteine absence in the conditioned media was able to reduce the formation of lipid droplets, which increased the greater access to free fatty acids to undergo oxidation, therefore inducing ferroptosis. On the contrary, cells when treated with deferoxamine along with erastin (ferroptosis-inducing drug), showed an increase in cell iron content was observed, later inducing ferroptosis. Conclusion: Our results show an alternative function of cysteine and deferoxamine, one regulating lipid droplets and the other inducing ferroptosis, although an inhibitor of the same, respectively.